'Block teaching' – exploring lecturers' perceptions of intensive modes of delivery in the context of undergraduate education. Issue 5 (27th May 2020) - Dixon, Laura; O'Gorman, Valerie
ABSTRACT: This article evaluates changes in teaching delivery during the first year of an undergraduate Tourism Management degree programme at a university in the North West of England. Moving from traditional semesterised mode, delivery was changed to shortened, time-intensive modules delivered one at a time, for two full days (six hours per day) over a three-week period. This was implemented in response to student feedback and concerns regarding student outcomes. Albeit limited, previous research suggests that intensive forms of delivery can improve engagement, attendance and attainment, particularly amongst students from diverse entry pathways. Although it is clear that the efficacy of block teaching relies heavily on – and creates new pressures for – teaching staff, little research has explored those impacts. Here instead, the perceptions of teaching staff were the focus. A qualitative approach was taken using an anonymous, online questionnaire, completed following one full year of block teaching. Findings suggest that, although most lecturers found that block teaching enabled them to manage their time more effectively, as the year progressed, block teaching negatively affected student attendance and subsequently hampered deep learning. Fully-integrated placement of assessment and use of one intensive module to aid transition was recommended to help overcome these issues.